Optimal Inequalities on (α,β)-Type Almost Contact Manifold with the Schouten–Van Kampen Connection - Mohd Danish Siddiqi; Ali H. Hakami (Axioms, 2023)
In the current research, we develop optimal inequalities for submanifolds in trans-Sasakian manifolds or <semantics>(α,β)</semantics>-type almost contact manifolds endowed with the Schouten–Van Kampen connection (<semantics>SVK</semantics>-connection), including generalized normalized <semantics>δ</semantics>-Casorati Curvatures (<semantics>δ</semantics>-CC). We also discuss submanifolds on which the equality situations occur. Lastly, we provided an example derived from this research.